Reflecting on the impact of the COVID pandemic on patient management and its subsequent influence on long-term outcomes: a case–control study in the field of esophago-gastric cancer - Mohamed Alasmar; Nadia Matias; Norah Ali M. Alhamed; Omneya Alwani; Brogan Rudge; Terngu David Moti; Muhammad Ossama Yassin Abdelwahab; Jennifer Stockton; Charef Raslan; Jess Cairney-Hill; Mohammad Altarawni; Bilal Alkhaffaf; et al. (World Journal of Surgical Oncology)
Abstract Background The delivery of cancer services changed significantly during the COVID-19 pandemic. This study aimed to describe changes in presentations, assess the change in recommendations by the MDT during the pandemic, and describe the subsequent long-term impact of these changes on survival rates in patients with EG cancer. Methods A retrospective cohort study was designed comparing three patient groups of those referred to EG MDT in the same 6-month period pre-pandemic (PP;2019) during the initial phase of the pandemic (P1;2020) and the year after the initial phase (P2;2021). The primary aim of this study was to describe and compare deviations from the standard of care across these three timeframes. Secondary outcomes included differences in the number of new cases with early and advanced oesophageal and gastric lesions, a comparison of survival rates among the groups, and an analysis of postoperative histopathology to identify any shifts in the tumour stage across the studied periods. Results A consistent demographic profile across these periods was maintained, but with a significant decrease in patient referrals during P1 (35.25% reduction from PP to P1 and 9.5% reduction from PP to P2), quicker ‘time to treatment’ during P1 (130.8 days in P1 vs 162 in PP and 178.9 in P2), and notable changes in treatment modalities. Additionally, we found an increased deviation from initial curative to palliative intent in the P2 group (6.4% changed in P2 vs 2.2% in PP and 3.5% in P2) primarily driven by disease progression. A further significant observation was the emergence of more aggressive tumour characteristics, particularly in the P2 group, albeit without a statistically significant difference in two-year overall survival rates among the groups (p-value 0.31). Conclusion The COVID-19 pandemic significantly impacted oesophagogastric cancer care, with a reduction in patient referral rates during the initial pandemic phase and a subsequent increase in more advanced stage disease. Our findings from a major UK EG centre highlight accelerated treatment decision-making during the initial pandemic phase was possible and that standard of care was maintained. These insights provide valuable lessons for healthcare systems in managing cancer care during global health emergencies.